Inferior In Vivo Osteogenesis and Superior Angiogeneis of Human Adipose‐Derived Stem Cells Compared with Bone Marrow‐Derived Stem Cells Cultured in Xeno‐Free Conditions. (19th October 2017) - Brennan, Meadhbh A.; Renaud, Audrey; Guilloton, Fabien; Mebarki, Miryam; Trichet, Valerie; Sensebé, Luc; Deschaseaux, Frederic; Chevallier, Nathalie; Layrolle, Pierre
Abstract: The possibility of using adipose tissue‐derived stromal cells (ATSC) as alternatives to bone marrow‐derived stromal cells (BMSC) for bone repair has garnered interest due to the accessibility, high cell yield, and rapid in vitro expansion of ATSC. For clinical relevance, their bone forming potential in comparison to BMSC must be proven. Distinct differences between ATSC and BMSC have been observed in vitro and comparison of osteogenic potential in vivo is not clear to date. The aim of the current study was to compare the osteogenesis of human xenofree‐expanded ATSC and BMSC in vitro and in an ectopic nude mouse model of bone formation. Human MSC were implanted with biphasic calcium phosphate biomaterials in subcutis pockets for 8 weeks. Implant groups were: BMSC, ATSC, BMSC and ATSC mixed together in different ratios, as well as MSC primed with either osteogenic supplements (250 μM ascorbic acid, 10 mM β‐glycerolphosphate, and 10 nM dexamethasone) or 50 ng/ml recombinant bone morphogenetic protein 4 prior to implantation. In vitro results show osteogenic gene expression and differentiation potentials of ATSC. Despite this, ATSC failed to form ectopic bone in vivo, in stark contrast to BMSC, although osteogenic priming did impart minor osteogenesis to ATSC. Neovascularization was enhanced by ATSC compared with BMSC; however, less ATSC engrafted into the implant compared with BMSC. Therefore, in the content of bone regeneration, the advantages of ATSC over BMSC including enhanced angiogenesis, may be negated by their lack of osteogenesis and prerequisite for osteogenic differentiation prior to transplantation. Stem Cells Translational Medicine 2017;6:2160–2172 Abstract : Masson Trichrome staining of ectopic implantations of mesenchymal stem cells and BCP biomaterials after 8 weeks in vivo. Human bone marrow stem cells induce abundant bone formation (green), with embedded osteocytes (red arrow) and mature BM territories, while adipose tissue stem cells fail to demonstrate osteogenesis. Scale bar denotes 100 μm. Abbreviations: BCP, bi‐phasic calcium phosphate; BM, bone marrow.